Designing embedded Internet devices - DeMuth, Brian; Eisenreich, Dan. (Oxford : Butterworth-Heinemann, 2002)
Embedded internet and internet appliances are the focus of great attention in the computing industry, as they are seen as the future of computing. The design of such devices presents many technical challenges. This book is the first guide available that describes how to design internet access and communications capabilities into embedded systems. It takes an integrated hardware/software approach using the Java programming language and industry-standard microcontrollers. Numerous illustrations and code examples enliven the text. This book shows how to build various sensors and control devices that connect to the TINI interfaces, explains how to write programs that control them in Java, and then ties them all together in practical applications. Included is a discussion on how these technologies work, where to get detailed specifications, and ideas for the reader to pursue beyond the book. The accompanying CDROM includes Java source code for all the applications described in the book, as well as an electronic version of the text. *The first guide to designing internet access and communications capabilities into embedded systems *Takes an integrated hardware/software approach using the Java programming language an industry-standard *Accompanying CDROM includes Java source code for all the applications described in the book, as well as an electronic version of the text.
Computer networks -- Java essentials for embedded networked devices -- Overview of embedded networked devices -- Getting started with TINI -- The TINI hardware -- The TINI software -- Enhancing TINI -- TINI serial and parallel I/O -- 1-wire basics for TINI -- The I²C bus -- Controller area network -- Connecting TINI to an IP network -- A few final thoughts.
Includes CD-ROM.
Keywords: Embedded computer systems; Internet; Electronic books